Planning the Training Process for Qualified Greco-Roman Wrestlers - Tursunov Shukhrat Sabitjonovich (Zien Journals, 2022)
The article substantiates the methods of teaching the technical and tactical actions of GrecoRoman wrestlers in the annual cycle.
Keywords: physical development; technical training